Hypothermia ameliorates blast-related lifespan reduction of C. elegans - Nicholas B. Angstman (Nature Portfolio, 2018)
Abstract Blast-related mild traumatic brain injury induces significant long-term health issues, yet treatment procedures remain underdeveloped. Therapeutic hypothermia has been postulated as a potentially effective therapy. In a Caenorhabditis elegans model, we demonstrate a dose-dependent reduction in lifespan following exposure to blast-like shock waves. Using polyvinyl alcohol, we show that cavitation is a key injurious factor in the damaging shock wave component. Short and long lifespan C. elegans mutants demonstrated the interaction of genetic and environmental longevity-determining factors. Hypothermia reduced the long term effect of shock wave exposure. Thus, we present an effective C. elegans model of long term effects of blast-related mild traumatic brain injury, as well as evidence of the merit of therapeutic hypothermia as a therapy option following blast exposure.